Mechanism of heat transfer with Nanofluids for the application in oil wells - A.H. Bhat; Imran Khan; Irshad Ul Haq Bhat; H. Soleimani; Mohd Amil Usmani (Springer, 2017)
Nanofluid plays an important role in a drilling process which includes the removal of cuttings, lubricating, and cooling the drill bits. Nonetheless, production increases from the reservoirs which are non-conventional, and the stability and performance of conventional drilling fluids under high-temperature and high-pressure (HTHP) environment have apprehensiveness. Both water- and oil-based drilling fluids are likely to experience a number of degenerations such as degradation of weighting materials, gelation, and disintegration of polymeric additives under HTHP conditions. Lately, nanotechnology has shown a lot of promise in the oil and gas sectors, including nanoparticle-based drilling fluids. This chapter is focused on to explore the influence of nanoparticles on the heat transfer efficiency of drilling fluids to make the drilling phenomena smooth and cost effective. The chapter begins with explaining the importance of drilling fluid during the drilling process with a historical assessment of drilling fluid industry development. It is followed by definitions, uses, and types of drilling fluid as well as the additives that are appended to enhance drilling fluid performance. Moreover, the progress of the oil production industry from unconventional wells has been discussed after which the limitations and degradation of the traditional drilling fluid have been taken up. Finally, this chapter discusses the great potential of nanotechnology in solving drilling problems in addition to the technical and the economic benefits of using nanomaterials in drilling fluids before offering a brief conclusion.